2010
DOI: 10.1002/jsfa.4125
|View full text |Cite
|
Sign up to set email alerts
|

Fruit dry matter concentration: a new quality metric for apples

Abstract: Fruit DMC can therefore be measured before or at harvest, and be used to predict the sensory potential for the fruit after storage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
88
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(100 citation statements)
references
References 31 publications
10
88
2
Order By: Relevance
“…Knee and Smith (1989) evaluated 'Cox' apples and found that sugar content, malate and firmness after storage were closely correlated to those observed during harvest, with continuous decreasing acidity and increasing fruit sweetness. Palmer et al (2010) found a positive correlation between fruit dry weight and TSS in 'Royal Gala' and 'Scifresh' apples evaluated at harvest and after 6 and 12 weeks of storage, with values close to the present ones for MA and TSS correlations (Table 1). These authors also found a positive low correlation between dry weight and fruit firmness.…”
supporting
confidence: 87%
See 2 more Smart Citations
“…Knee and Smith (1989) evaluated 'Cox' apples and found that sugar content, malate and firmness after storage were closely correlated to those observed during harvest, with continuous decreasing acidity and increasing fruit sweetness. Palmer et al (2010) found a positive correlation between fruit dry weight and TSS in 'Royal Gala' and 'Scifresh' apples evaluated at harvest and after 6 and 12 weeks of storage, with values close to the present ones for MA and TSS correlations (Table 1). These authors also found a positive low correlation between dry weight and fruit firmness.…”
supporting
confidence: 87%
“…The evaluation of morphological/productive traits of apples before and during harvest can contribute to achieve fruits with higher commercial quality, especially regarding flesh firmness, titratable acidity, total soluble solids and juice content (Palmer et al 2010). Thus, studies of linear relations between apple traits can contribute to the indirect evaluation of harvesting time, quality and metabolic activity, allowing external rather than destructive evaluations of the fruits.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, a correlation between SSC and Young's modulus was anticipated as firmness was correlated with dry matter content (Palmer et al, 2010) and SSC represents the major part of dry matter. The lack of correlation observed may be the result of the small variation range compared to standard deviations in the fruit studied.…”
Section: Correlations Between Chemical Measurements and Mechanical Pamentioning
confidence: 99%
“…F ruit dry matter concentration (DMC) has recently been suggested as a key metric of fruit quality in apple at harvest (Palmer et al, 2010). The utility of this metric was evident in its ability not only to predict fruit soluble solids concentrations (SSC) after cool storage, but also to predict consumer liking.…”
mentioning
confidence: 99%